Correlation between the number of brushes per day and the dmft index in 12-year-old school children from the El Vecino parish in Cuenca, Ecuador 2016 - Fernández-Pesantez, Hannia Estefanía (2021)
Objective: Correlate the number of brushes per day and the decay-missing-filled teeth (DMFT) index in 12-year-old school children from the parish “El Vecino Cuenca - Ecuador 2016”. Materials and Methods: The study was communicational, quantitative, descriptive, and relational. The population consisted of 279 records from the study of the epidemiological map of schoolchildren in the “El Vecino” parish. The database included the registration number, age, sex, parish and DMFT Index. Results: There was an statistically significant inverse correlation between the number of brushes per day and the DMFT index with a p value = 0.029. Conclusion: The present study shows that there is a correlation between the number of brushes per day and the DMFT index.